Development of gas detection and database systems on cupping practice (circuit and hardware) - Razlan Hafeez, Ramle (2022)
This paper describes the design of a cupping practice gas detection with database. Dry and wet cupping are the two most popular types of cupping therapy. Wet cupping lacerates the skin, allowing blood to be sucked into the cup. The goal of modern medicine is to detect and understand the effects of Cupping Therapy. The problem statement for this project is that the gas produced inside the cup during cupping can both signal the patient's health and be dangerous to the practitioner. Also, the cupping patient's health (gases expelled during cupping) is unknown. The goal is to construct a sensor array for gas detection. The second goal is to create a GUI (Graphical User Interface). The third goal is to practice dry and wet cupping. We begin dry and wet cupping after constructing the hardware for the cupping device. The sensors will detect gases once implanted on the human body. The sensor reading will be shown on the app. The sensor data will then be sent to the Blynk application. The data will then be manually entered into the GUI. Finally, the PhPMyAdmin software will store each patient's data in a database.